Direct factor IXa inhibition with the RNA-aptamer pegnivacogin reduces platelet reactivity in vitro and residual platelet aggregation in patients with acute coronary syndromes. Issue 6 (1st September 2019) - Staudacher, Dawid L; Putz, Vera; Heger, Lukas; Reinöhl, Jochen; Hortmann, Marcus; Zelenkofske, Steven L; Becker, Richard C; Rusconi, Christopher P; Bode, Christoph; Ahrens, Ingo
Abstract: Background: Residual platelet reactivity is a predictor of poor prognosis in patients with acute coronary syndromes (ACSs) undergoing percutaneous coronary intervention. Thrombin is a major platelet activator and upon initiation of the coagulation cascade, it is subsequently produced downstream of factor IXa, which itself is known to be increased in ACS. Pegnivacogin is a novel RNA-aptamer based factor IXa inhibitor featuring a reversal agent, anivamersen. We hypothesized that pegnivacogin could reduce platelet reactivity. Methods: Whole blood samples from healthy volunteers were incubated in vitro in the presence and absence of pegnivacogin and platelet reactivity was analysed. In addition, platelet aggregometry was performed in blood samples from ACS patients in the RADAR trial featuring the intravenous administration of pegnivacogin as well as reversal by anivamersen. Results: In vitro, pegnivacogin significantly reduced adenosine diphosphate-induced CD62P-expression (100% vs . 89.79±4.04%, p =0.027, n =9) and PAC-1 binding (100% vs . 83.02±4.08%, p =0.010, n =11). Platelet aggregation was reduced (97.71±5.30% vs . 66.53±9.92%, p =0.013, n =10) as evaluated by light transmission aggregometry. In the presence of the RNA-aptamer reversal agent anivamersen, neither CD62P-expression nor platelet aggregation was attenuated. In patients with ACS treated with aspirin and clopidogrel, residual platelet aggregation was significantly reduced 20 min after intravenous bolus of 1 mg/kg pegnivacogin (100% versus 43.21±8.23%, p =0.020). Conclusion: Inhibition of factor IXa by pegnivacogin decreases platelet activation and aggregation in vitro. This effect was negated by anivamersen. In ACS patients, platelet aggregation was significantly reduced after intravenous pegnivacogin. An aptamer-based anticoagulant inhibiting factor IXa therefore might be a promising antithrombotic strategy in ACS patients.